2020
DOI: 10.1021/acs.jpclett.0c00591
|View full text |Cite
|
Sign up to set email alerts
|

Nanoconfined Fluids: What Can We Expect from Them?

Abstract: Nanoconfined fluids (NCFs), which are confined in nanospaces, exhibit distinctive nanoscale effects, including surface effects, small-size effects, quantum effects, and others. The continuous medium hypothesis in fluid mechanics is not valid in this context because of the comparable characteristic length of spaces and molecular mean free path, and accordingly, the classical continuum theories developed for the bulk fluids usually cannot describe the mass and energy transport of NCFs. In this Perspective, we su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 195 publications
0
43
0
1
Order By: Relevance
“…Configurations of water confined in graphene nanochannels are different from those in bulk due to the confinement effects by the channel walls (Sun et al, 2020;Zhou et al, 2021;Zhao et al, 2020a;Zhao et al, 2020b;Zhao et al, 2020c). Specifically speaking, the repulsive force confines the water molecules in the nanochannel, while the potential well or adsorption interaction changes the structure of confined water (Zhao et al, 2020b).…”
Section: Density Distribution and Hydrogen Bondmentioning
confidence: 99%
See 1 more Smart Citation
“…Configurations of water confined in graphene nanochannels are different from those in bulk due to the confinement effects by the channel walls (Sun et al, 2020;Zhou et al, 2021;Zhao et al, 2020a;Zhao et al, 2020b;Zhao et al, 2020c). Specifically speaking, the repulsive force confines the water molecules in the nanochannel, while the potential well or adsorption interaction changes the structure of confined water (Zhao et al, 2020b).…”
Section: Density Distribution and Hydrogen Bondmentioning
confidence: 99%
“…As the sizes of many devices such as lab-onchips, NEMS, and electronic chips are reduced to nanoscale, rapid heat dissipation becomes a challenge restricting the development of nanodevices (Lee et al, 2013). The thermophysical properties of nanoconfined water (Sun et al, 2020), especially specific heat capacity, determines whether it can still function at nanoscales.…”
Section: Introductionmentioning
confidence: 99%
“…This enhancement of the molecular permeance is caused by the relatively stronger CO 2 adsorption abilities on the hBN surfaces compared with those on the graphene surface. It is expected that this type of graphene nanopores are promising for high-efficiency membranes for molecular separation as well as other processes involving molecular permeation (Sun et al, 2020b). This work presents a promising road to achieve ultrapermeable porous membranes even with a higher molecular permeability compared to the single-layer membranes.…”
Section: Introductionmentioning
confidence: 98%
“…The molecular arrangement and orientation in the static state, and the dynamic properties can be measured on a length scale from µm to nm owing to the progress in experimental techniques such as atomic force microscopy (AFM) 8 , surface force apparatus (SFA) 9 , and resonance shear measurement (RFM) 10 . Confined liquids exhibit distinct phases 11,12 and flow properties 13,14 not exhibited in the bulk solution even for low-molecular-weight solutions such as water owing to the effect of spatial constraints and solid-liquid interfaces. Confined water is an interesting system because it is ubiquitous in nature; examples include biochannels 15,16 and water films confined between clay mineral surfaces 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Pure water and lubricating oil with trace quantities of water are also potential candidates for future lubricants due to their eco-friendly nature. 14,19,20 A recent experiment 20 conducted on hexadecane with trace quantities of water confined between mica walls demonstrated that the nucleation of water nanodroplets at the surface is induced by an increase in the temperature of the system, and the addition of amphiphilic molecules such as oleic acids to the lubricant suppresses this nucleation. Additionally, research conducted on the viscosity behavior of four different phenyl ether lubricants under nanoslit confinement using RSM indicated a significant increase in the viscosity with the decrease in the surface separation ( 2 nm), and the magnitude of the viscosity correlation between the bulk and the confined systems was reversed.…”
Section: Introductionmentioning
confidence: 99%